Kebahagiaan Santri Penghafal Al-Qur’an Ditinjau dari Regulasi diri (The Happiness of Islamic Boarding School Students Who Memorize the Qur’an: The Role of Self-Regulation) - Pratiwi, Riah (Happiness: Journal of Psychology and Islamic Science, 2026)
Students who memorize the Qur’an have dynamics that indicate that they carry dual responsibilities as academic learners and guardians of memorization, requiring strong self-regulation that ultimately influences their level of happiness. This study has three objectives: (1) to identify the variation of self-regulation among Qur’an-memorizing students at the Hamalatil Qur’an; (2) to identify the variation of happiness among these students; and (3) to examine the corelations between self-regulation and happiness in Qur’an-memorizing students at the same institution. This study employed a correlational design with a quantitative approach. The study population consists of 130 Qur’an-memorizing students, and the sample was selected using a purposive sampling technique, resulting in 57 individuals who met the criteria. The research findings show that variations in self-regulation are mostly categorized as high, with 30 students (52.6%), while the remaining 27 students (47.4%) fall into the moderate category. Furthermore, variations in happiness among the students predominantly fall within the moderate category, represented by 37 students (64.9%), followed by 20 students (35.1%) in the high category. Self regulation and happiness in Qur’an-memorizing students have a significant relationship, which is reflected in the correlation coefficient obtained is r = 0.684 with a significance value of p = 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) is accepted. This means that higher levels of self-regulation tend to correspond with higher levels of happiness among students who must balance the demands of memorizing the Qur’an while managing their academic responsibilities at the Islamic boarding school.